Towards strengthening Shariah governance: a conceptual framework on the need for external Shariah audit in Malaysian Islamic financial institutions - Mohd Zamri, Muhammad Mundzir; Asni, Fathullah; Rosman, Romzie (HRMARS, 2025)
Shariah audit is a crucial instrument in ensuring that Islamic financial institutions (IFIs) comply with Shariah principles. In Malaysia, Shariah governance has been strengthened through the introduction of the Shariah Governance Framework (BNM, 2010) and the Shariah Governance Policy (BNM, 2019), which emphasize the roles of Shariah review, risk management, and internal Shariah audit. However, the aspect of external Shariah audit has not yet received adequate attention. The absence of a clear structure, standards, and specific guidelines has raised various issues concerning auditor competency, independence, audit firm transparency, and the overall effectiveness of Shariah compliance mechanisms within IFIs. These challenges undermine public confidence in the integrity of the Islamic financial system and highlight the need to institutionalize external Shariah audit as an independent body. Accordingly, the objective of this study is to conceptually examine the necessity of external Shariah audit for IFIs in Malaysia. This study adopts a conceptual literature review methodology, drawing on previous research related to Shariah governance, internal and external auditing, auditor competency, as well as international standards such as AAOIFI and IFRS. The review yields three key findings. First, external Shariah audit is seen as a complement to internal Shariah audit in providing independent assurance of Shariah compliance. Second, there exists a significant gap in Shariah audit standards and guidelines, necessitating the development of a more systematic framework and professional accreditation for Shariah auditors. Third, effective external Shariah audit has the potential to enhance Muslim customers’ confidence, strengthen market reputation, and improve the transparency of IFIs’ operations in Malaysia. This study concludes that the implementation of external Shariah audit is a critical requirement for reinforcing the integrity of Shariah governance. Future research is recommended to adopt empirical approaches whether qualitative, quantitative, or mixed methods to evaluate the direct impact of external Shariah audit on financial performance and public confidence in IFIs.